THE INFLUENCE OF LIVE STREAMING, VIRAL MARKETING, CASH ON DELIVERY PAYMENT SYSTEM, AND ONLINE CUSTOMER REVIEWS ON PURCHASING DECISIONS AT TIKTOK SHOP CASE STUDY ON TIKTOK SHOP USERS IN SEMARANG CITY - Aditya, Didik; Ismail, Harries Arizonia (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyse the effect of live streaming, viral marketing, cash on delivery payment system, and online customer reviews on purchasing decisions at TikTok Shop. This study focuses on TikTok Shop users in Semarang City with an age range of 18-30 years. This research is important to understand how digital marketing strategies influence consumer behaviour on social media-based e-commerce platforms. The research method used is a quantitative approach with survey techniques through distributing questionnaires. A sample of 100 respondents was obtained using purposive sampling method. The data collected was analysed using multiple linear regression with the help of SPSS software to test the influence of variables both partially and simultaneously. The results showed that partially, live streaming, viral marketing, cash on delivery payment system, and online customer reviews have a positive and significant effect on purchasing decisions. Simultaneously, the four variables also have a significant influence on purchasing decisions. These findings confirm the importance of integrating interactive and trust-based marketing strategies in driving consumer purchasing decisions in the digital era.